A importância das estratégias de leitura na produção das codas silábicas em /R/, /L/ e /S/ mediais e finais - Fonseca, Regina Araújo da (2015)
Reading acquisition is a complex process, which includes several concepts from the simplest and primary such as decoding signs, to the fullest, as we see Martins (2012), Fernandes (2010), who consider reading much more than the simple action of translating language codes. This research used the qualitative method in order to be exploratory, aiming to provide greater familiarity with the problem in order to make it explicit or build hypotheses, involving literature review and analysis of the activities, which encouraged understanding the phenomenon under study. The research also used the technique of observation and systematization of data collection, in order to identify the determinants of the phenomenon, which favor the occurrence of the same.Fieldwork was in a municipal public school in the city of Recife, in Pernambuco. At first there were, initially, six students in this research, but as appropriate to what the research proposed, the number changed to four, this enabled a transformation of the students’ role in the reading classes. The weak points in the learning of the reading process were identified, and the activities with specific reading strategies, that were used as a support to remedy the difficulties presented by the students of the third grade of elementary school 1. Production was analyzed in order to verify whether or not there is the deletion of the coda in /r/, /s/ and /l/medial and final, for language deletion of syllable codas performed in readings. After the intervention process it was found that with the application of consistent reading strategies, participants developed a production of syllabic coda in /r/, /s/ and /l/ medial and final. And identify the degree of complexity of the reading of the focus on students and the reading of the focus on students and the reading level of each student was at the beginning during the process and the final phase of the development of research.